2009
DOI: 10.1063/1.3152293
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted three-dimensional multilayer magnetic recording

Abstract: Layer-selective writing of two layer bit patterned media is demonstrated by performing micromagnetic finite element simulations. Selectivity is achieved by controlling the frequency of an oscillating magnetic field in the gigahertz range, applied in addition to the head field. Generation of the microwave field by means of a wire next to the tip of a single pole head is proposed. The Oersted field from the alternating current induces magnetic oscillations in the pole tip which create a high frequency field that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…Given these circumstances, three-dimensional (3D) magnetic recording with multiple recording layers has been proposed [3][4][5][6][7][8][9][10][11][12][13]. According to previous studies on field-induced switching for 3D devices [3][4][5][6], when each of the multiple recording layers is provided with a different coercive field ( c ), magnetization manipulation is accomplished by switching the layers sequentially in order from the one with the largest c to the one with the lowest c .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given these circumstances, three-dimensional (3D) magnetic recording with multiple recording layers has been proposed [3][4][5][6][7][8][9][10][11][12][13]. According to previous studies on field-induced switching for 3D devices [3][4][5][6], when each of the multiple recording layers is provided with a different coercive field ( c ), magnetization manipulation is accomplished by switching the layers sequentially in order from the one with the largest c to the one with the lowest c .…”
Section: Introductionmentioning
confidence: 99%
“…To solve this problem, a writing method that can conduct single-step magnetization switching selectively in a specific recording layer is required. To realize this, we focus on microwave-assisted magnetization switching (MAS) [7][8][9][13][14][15][16][17][18][19][20][21][22][23]. Recent studies on MAS have revealed that reduction in the switching field (H sw ) of a magnet depends on the frequency of the applied microwave field ( rf ), which is related to the ferromagnetic resonance (FMR) frequency of the magnet [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Alternate magnetic dual-layer media using oblique evaporated Co-CoO medium has also been proposed as a method of recording on more than one layer [22] . Finally, implementation of microwave assisted magnetic recording was also considered for dual-layer ML-3D recording [23] , [24] .…”
Section: Introductionmentioning
confidence: 99%
“…This grants SWAS the merit of large H sw reduction at relatively low f . In addition, the three-dimensional magnetic recording using multilevel media has been intensively studied in recent years in order to further increase the recording density [16][17][18][19][20] . Realizing it requires a recording technique having the ability to selectively switch the magnetization of a desired layer without interfering the neighboring layers.…”
mentioning
confidence: 99%